1999
DOI: 10.1111/j.1349-7006.1999.tb00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Intracellular Distribution of Amrubicin, a Novel 9‐Amino‐anthracycline, and Its Active Metabolite Amrubicinol in P388 Murine Leukemia Cells

Abstract: Amrubicin, a 9-aminoanthracycline anti-cancer drug, and its C-13 hydroxyl metabolite amrubicinol, were examined for growth-inhibitory activity as well as cellular uptake and distribution in P388 murine leukemia cells and doxorubicin-resistant P388 cells. Also discussed are the differences in the mechanisms of action among amrubicin, amrubicinol and doxorubicin in terms of their cellular pharmacokinetic character. In P388 cells, amrubicinol was about 80 times as potent as amrubicin, and about 2 times more poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Interestingly, previous reports have suggested that other anthracyclines may also act through regulating both internal and external membrane structures in the cell, such as binding to the phospholipid cardiolipin on the mitochondrial membrane and peroxidation of membrane-unsaturated lipids in the cytoplasmic compartment [31]. Our data are similar to those reported by Yamaoka et al [32] who observed that amrubicin remained active and cytotoxic in doxorubicin-resistant P388 murine leukemia cells. Although amrubicin could be a weak P-glycoprotein substrate, our experiments demonstrate that P-glycoprotein inhibitors do not affect the accumulation of amrubicin in doxorubicin-resistant cells.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, previous reports have suggested that other anthracyclines may also act through regulating both internal and external membrane structures in the cell, such as binding to the phospholipid cardiolipin on the mitochondrial membrane and peroxidation of membrane-unsaturated lipids in the cytoplasmic compartment [31]. Our data are similar to those reported by Yamaoka et al [32] who observed that amrubicin remained active and cytotoxic in doxorubicin-resistant P388 murine leukemia cells. Although amrubicin could be a weak P-glycoprotein substrate, our experiments demonstrate that P-glycoprotein inhibitors do not affect the accumulation of amrubicin in doxorubicin-resistant cells.…”
Section: Discussionsupporting
confidence: 94%
“…5 Amrubicin is a totally synthetic 9-aminoanthracycline anticancer drug and a potent inhibitor of topoisomerase II. [6][7][8][9][10][11][12][13] It is similar in chemical structure to a representative anthracycline, doxorubicin, but it is more potent than doxorubicin against various mouse experimental tumors and human tumor xenografts. Amrubicin is converted to an active metabolite, amrubicinol, through the reduction of its C-13 ketone group to a hydroxy group.…”
Section: Introductionmentioning
confidence: 99%
“…Although classified as anthracycline agents, amrubicin and amrubicinol exert cytotoxic effects as DNA topoisomerase II inhibitors, but not mainly as DNA intercalators. [10][11][12][13][14][15][16][17] A Japanese phase II study with intravenous administration of single-agent AMR at 40 mg/m 2 for three consecutive days in previously treated SCLC patients was reported. The overall RRs were 52, 50% in sensitive and refractory relapse cases respectively.…”
Section: Discussionmentioning
confidence: 99%